2019
DOI: 10.1007/s11894-019-0728-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Control of Esophageal Peristalsis and Its Role in Esophageal Disease

Abstract: Purpose of Review Esophageal peristalsis is a highly sophisticated function that involves the coordinated contraction and relaxation of striated and smooth muscles in a cephalocaudal fashion, under the control of central and peripheral neuronal mechanisms and a number of neurotransmitters. Esophageal peristalsis is determined by the balance of the intrinsic excitatory cholinergic, inhibitory nitrergic and post-inhibitory rebound excitatory output to the esophageal musculature. Recent Findings Dissociation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 126 publications
0
13
0
1
Order By: Relevance
“…SGB can induce reflux, the mechanism of which is unclear ( Figure 1 B). There are three possibilities as follows: (1) SGB-induced esophageal distension might provoke A TLESR [ 37 , 38 ], (2) AN INCREASE IN abdominal pressure might bring up the gastric contents through the LES, (3) TLESR might elicit a reflex of UES relaxation, which IN TURN lets the air into the esophagus [ 39 ]. Glasinovic et al showed that 26% of total acid exposure time is caused by SGB-induced reflux in GERD patients with excessive SGB [ 3 ].…”
Section: Belching and Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…SGB can induce reflux, the mechanism of which is unclear ( Figure 1 B). There are three possibilities as follows: (1) SGB-induced esophageal distension might provoke A TLESR [ 37 , 38 ], (2) AN INCREASE IN abdominal pressure might bring up the gastric contents through the LES, (3) TLESR might elicit a reflex of UES relaxation, which IN TURN lets the air into the esophagus [ 39 ]. Glasinovic et al showed that 26% of total acid exposure time is caused by SGB-induced reflux in GERD patients with excessive SGB [ 3 ].…”
Section: Belching and Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…17,[21][22][23] Secondary peristalsis functions to clear the esophagus of retained or refluxed esophageal contents and maintain an empty esophagus. 21,22,[24][25][26] On the other hand, primary peristalsis (which is typically evaluated by HRM) is the principle form of esophageal motility triggered by swallowing that facilitates bolus transit to the stomach. 11 Similar to primary peristalsis, abnormal secondary peristalsis can lead to dysphagia and pathologic acid reflux.…”
Section: Physiologic Parameters and Motility Patterns Obtained By Flipmentioning
confidence: 99%
“…Основные нарушения перистальтики: спастические нарушения двигательной функции пищевода (дистальный эзофагоспазм, гиперконтрактильный пищевод) и отсутствие перистальтики В основе регуляции моторики пищевода лежит взаимодействие нервных и гуморальных факторов. При нарушении координированного действия тормозящих и возбуждающих систем регуляции возникает патологическая сократительная активность, проявляющаяся гипер-или гипомоторной дискинезией [35,36].…”
Section: нарушения двигательной функции грудного отдела пищеводаunclassified